Mg2+ ion-catalyzed polymerization of 1, 3-dioxolane in battery electrolytes. Issue 33 (24th March 2020) - Sahadeo, Emily; Wang, Yang; Lin, Chuan-Fu; Li, Yue; Rubloff, Gary; Lee, Sang Bok
Abstract : Mg 2+ ions in electrolytes can catalyze the polymerization of 1, 3-dioxolane to form poly-DOL while anion pairs affect their capability. Abstract : Electrolyte salts with Mg 2+ and Al 3+ Lewis acidic cations demonstrate polymerization of 1, 3-dioxolane. The speed and extent of the reaction depends on coordination of the anion with the Mg 2+ cation catalyst. Weakly coordinating anions such as TFSI − aid faster polymerization while strongly coordinating anions such as ClO4 − hinder the polymerization.